UPLC-HRMS and NMR applied in the evaluation of solid-phase extraction methods as a rational strategy of dereplication of Phyllanthus spp. aiming at the discovery of cytotoxic metabolites - Silva, Maria Francilene Souza; Silva, Lorena Mara A.; Quintela, Amanda Lemos; dos Santos, André Gonzaga [UNESP]; Silva, Francisca Aliny Nunes; de Oliveira, Fátima de Cássia E.; Alves Filho, Elenilson Godoy; de Brito, Edy Sousa; Canuto, Kirley Marques; Pessoa, Claudia; Zocolo, Guilherme Julião (Elsevier, 2019)
The classical approach to drug discovery from natural products (NP's) requires strenuous and complex purification steps for the isolation and structural elucidation. Modern strategies as dereplication aim to accelerate the identification of known compounds present in a crude or partially purified extract. In this work, we investigated the influence of the solid-phase extraction (Oasis, Plexa, and Agilent C18 cartridges with and without organic modifiers) chemical profile obtained by UPLC-QTOF-MS and NMR and cytotoxicities of aqueous extracts from Phyllanthus niruri and P. amarus. Our results showed differences between the SPE cartridges and the mass recovered. P. niruri showed higher mass recovery than P. amarus indicating a higher amount of secondary metabolites. The UPLC-QTOF-MS analysis revealed that P. niruri crude extract presents higher contents of phenolic compounds than P. amarus. According to NMR analysis, P. niruri contained more tyrosine, corilagin, and glycosidic residues while P. amarus, presented higher content of ellagic acid. The different stationary phases, as well as mobile phases for exploratory SPE, enabled the exploitation of the different chemical functionalities within the Phyllanthus species. The SPE (MeOH:H 2 O 70:30 with C18 cartridges) samples showed greater in vitro cytotoxicity than the crude extracts, with IC 50 ranging from 8.01 to 94.92 μg mL −1 against the tumor lines tested. The solid phase extraction allowed the concentration of molecules with desirable physicochemical characteristics, which might increase the hit of therapeutically useful substances.
Keywords: Cancer; Cytotoxicity; Dereplication; Phyllanthus spp.; “Stone break”